2007
DOI: 10.1002/app.26346
|View full text |Cite
|
Sign up to set email alerts
|

Network structure and properties of polyurethanes from soybean oil

Abstract: Vegetable oils are very heterogeneous materials with a wide distribution of triacylglycerol structures and double-bond contents. The hydrogenation of epoxidized soybean oil (ESO) produces polyols having a functionality distribution related to that of soybean oil. Therefore, these polyols are convenient substances for studying the impact of structural heterogeneity on network formation and properties. Polyols of hydroxyl numbers ranging from 225 to 82 mg KOH/g and weight-average functionalities ranging from 4.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 15 publications
6
88
0
Order By: Relevance
“…Depending on the type of decomposition mechanism, the resulting degradation products may include alcohols, amines, olefins, carbon dioxide, and fatty acid chain scission. [25][26][27][28] The temperature at the maximum degradation rate of the alkali lignin is 267°C, while the temperature of the maximum degradation rate of QLD is 300°C. Comparing alkali lignin with QLD shows that the thermostability of QLD prevailed over alkali lignin.…”
Section: X-ray Diffraction Spectroscopy Analysismentioning
confidence: 99%
“…Depending on the type of decomposition mechanism, the resulting degradation products may include alcohols, amines, olefins, carbon dioxide, and fatty acid chain scission. [25][26][27][28] The temperature at the maximum degradation rate of the alkali lignin is 267°C, while the temperature of the maximum degradation rate of QLD is 300°C. Comparing alkali lignin with QLD shows that the thermostability of QLD prevailed over alkali lignin.…”
Section: X-ray Diffraction Spectroscopy Analysismentioning
confidence: 99%
“…Moreover, life cycle assessment of vegetable oil polyols shows environmental benefits like reduction in the demand of fossil resources and formation of very low greenhouse gas emission [4]. Therefore, the hydroxylated derivatives of vegetable oils are interesting and alternative replacements for petrochemical polyols in the synthesis of PUR materials [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the content of unsaturated bonds in various oils confirmed that palm oil is a convenient raw material for the synthesis of the polyols with low and medium content of hydroxyl groups [16]. Low content of unsaturated bonds (LI = 50-55) in palm oils allows to obtain (using the epoxidation method followed by ring opening) the products with hydroxyl numbers lower than 200 mg KOH/g and very low content of unreacted double bonds [7]. Additionally, palm oil is the cheapest among the ones currently produced vegetable oils and had the largest contribution of the total production in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The polyols discussed so far are of relatively low molar mass (~1000) and hydroxyl equivalent (200-300), suitable for rigid and semi-rigid applications (rigid foams, cast resins, coatings and adhesives). Another issue with these polyols is a wide functionality distribution ranging from 1 to 8 OH groups per molecule [19].…”
Section: Scheme 8 Hydroformylation Reactionmentioning
confidence: 99%